The Influence of School Principals’ Leadership, Teacher Performance on 21st-Century Learning Characteristics Among High School Students in Pandeglang - Ahmadi Ahmadi; M. Syadeli Hanafi; Ujang Jamaludin (MASI Mandiri Edukasi, 2026)
The growing demand for 21st-century learning skills—such as critical thinking, creativity, collaboration, and communication—poses a significant challenge in secondary education, particularly when instructional leadership, teacher competence, and classroom performance are not optimally aligned. This study addresses the question of whether school principals’ leadership and teacher performance, directly or indirectly, influence the development of 21st-century learning characteristics among high school students. The objective is to identify and analyze both the direct and indirect effects of these three factors on students’ 21st-century learning characteristics. A quantitative descriptive research design was employed, using purposive sampling of selected high schools in Pandeglang. Data were collected through questionnaires and documentation and analyzed using path analysis and multiple regression. The findings reveal that school principals’ leadership and teacher performance each have a significant positive influence, both partially and simultaneously, on 21st-century learning characteristics among high school students in Pandeglang. These results underscore the importance of integrating leadership development, teacher competency training, and performance evaluation to foster 21st-century skills in secondary education.